Asterion, the myth reinvented by Borges with burlesque overtones - Maria Stella Galvão Santos (2i Revista de Estudos de Identidade e Intermedialidade)
In the face of strange, bizarre or tragically symbolic beings, the mechanisms of humour will be responsible for linking, through parody or irony, a story that even reverts to the mythological. This is what the Argentinian Jorge Luis Borges does in the short story “La casa de Asterión” [The House of Asterión] [El Aleph, 1949]. It is a short story that proposes a new look at the Greek myth of the Minotaur. Borges rewrites the myth and adds new possibilities of representation to the one whose reference comes, in mythology, as a synonym of horror and human sacrifice. In truth, what the writer does is a form of mythocriticism, with which the drama of Asterion reaches and plays with the limits of the burlesque.